Non-Linear Berger’s Coefficient Prioritization for Quality of Sustainability in Healthcare Services - Cheng, Ching Yong (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2018)
Link to publisher's homepage at http://amci.unimap.edu.my